PENGEMBANGAN MEDIA KOMIK BERBASIS KEARIFAN LOKAL PEMBELAJARAN IPAS PADA MATERI ANCAMAN KRISIS ENERGI KELAS V SD: PENGEMBANGAN MEDIA KOMIK BERBASIS KEARIFAN LOKAL PEMBELAJARAN IPAS PADA MATERI ANCAMAN KRISIS ENERGI KELAS V SD - Nabila Miranda; Tika Dwi Nopriyanti; Puji Ayurachmawati (STKIP Subang, 2025)
Comic media development research to determine the validity and practicality of the comic media developed. This type of research is Research and Development (R&D) with the ADDIE method consisting of Analysis, Design, Development, Implementation, and Evaluation. Comic media is a fun and affective method to convey in science learning. By using interesting images and text, comics can make fifth grade students easier to understand the material through more relaxed and simple dialogue, so that students feel entertained and not bored while learning. The results of the research from the development of comic media are stated to be valid and practical as seen through expert validation questionnaire data with an average value of 90.1% it is said that the comic media that has been developed can be categorized as very valid. very practical through student response questionnaires with an average value of 96,8% at the one to one stage, an average percentage value of 90.2% at the Small Group stage, and an average percentage value of 90.6% at the field test stage with very practical criteria.